Effects of dietary rumen-protected glucose level and taurine supplementation on weight change and oxidative stress state of yaks after transport - Wang, Xiaolin; Zhao, Kaiqiang; Zhao, Shoupei; Zhou, Jia; Cao, Mingyu; Lu, Lianghao; Chen, Yuanyuan; Yang, Huaming; Zhang, Bao; Shao, Chong; Zhao, Yanfei; Tang, Rui; et al. (Frontiers in Veterinary Science, 2024)
Rumen-protected glucose (RPG) and taurine (TAU) are crucial for the nutrition and physiology of ruminants, enhancing production performance and mitigating negative energy balance. This study aimed to assess the impact of RPG levels and TAU supplementation on the body weight, antioxidant capacity, immune function and stress responses in yaks before and after transport. Thirty-two healthy male yaks, aged 3 years and weighing 172.5 ± 10.2 kg, were randomly assigned to one of four dietary treatments: (1) low RPG and low TAU (LRLT), with 1% RPG and 5 g/d TAU; (2) low RPG and high TAU (LRHT), with 1% RPG and 15 g/d TAU; (3) high RPG and low TAU (HRLT), with 3% RPG and 5 g/d TAU; and (4) high RPG and high TAU (HRHT), with 3% RPG and 15 g/d TAU. The yaks were treated with the corresponding diet for 7 days, then received 9 h of transportation, and finally fed the same diet at their destination for 30 days. The weight was measured before and on days 0 and 30 after transport, and the plasma was collected before and on day 0, 10, and 30 after transport for analysis of biochemical, antioxidant, immune, and stress response indicators. We observed that transport increased plasma concentrations of total cholesterol, total protein, lactate dehydrogenase, creatine kinase, malondialdehyde, cortisol and lipopolysaccharides of yaks among treatments, while decreased their BW and plasma IL-10 concentration. Increasing TAU supplementation reduced weight loss (8.42 vs. 11.9 kg) and weight loss percent (4.83% vs. 6.87%) in yaks after transport. The concentration of MDA in plasma was lower in HRHT than in LRLT at day 0 after transport (p = 0.03). The activity of GSH-PX was higher in HRHT than in LRLT at day 10 after transport (p = 0.04). Concentrations of IL-10 at day 0 and 10 after transport was higher in HRHT than in LRLT and HRLT (p = 0.02, p = 0.01, respectively). With the increase of TAU supplementation, concentrations of IL-1β at day 30 after transport (p = 0.02), TNF-α at day 0 after transport (p = 0.02), COR at day 10 (p = 0.03) and 30 (p = 0.05) after transport as well as LPS at day 0 after transport (p = 0.04) decreased. In addition, concentrations of COR at day 0 after transport was lower in LRHT and HRHT than in LRLT (p = 0.03). Based on all the results, we demonstrated that increasing TAU supplementation levels reduced post-transport weight loss in yaks, improved their antioxidant capacity and immune function, and alleviated stress responses. Considering the effect of resistance to transport stress and costs, the optimal treatment identified in this study involved a diet containing 1% RPG and supplemented with 15 g/d TAU.